Agroecological approaches to securing rural livelihoods: a critical analysis using the example of Tanzania - Ahmad, Nadja; Köpke, Sören (Frontiers in Sustainable Food Systems, 2024)
Agrifood systems globally are confronted with mounting challenges, including hunger, rising food prices, and geopolitical tensions. Conventional agricultural models face criticism for causing environmental degradation and increasing poverty, which emphasizes the need for sustainable alternatives. Agroecology emerges as a promising solution that embodies a holistic, farmer-centric countermovement against corporate-led food systems. However, the practical implementation of agroecology as practice, science and social movement faces considerable barriers. Sceptics argue that agroecology is too complex, labor- and knowledge-intensive and cannot keep up with the production level of conventional agriculture. The case study was conducted in Tanzania’s Southern Highlands, based on expert interviews and literature analysis. It finds 18 factors that potentially impede the implementation and dissemination of agroecological approaches. Impeding factors exist in all three agroecological approaches. Most obstacles were identified with agroecology as a practical approach. Agroecology as a social movement was only addressed to a limited extent. Main challenges within the approaches include the fear of high financial, time, and energy expenditures when implementing agroecology, difficulties in adopting agroecological practices, the desired and equal collaboration between farmers and researchers, diverging and different definitions and understandings of agroecology, gender relations in farming activities and market and price dependencies for generating income. The study emphasizes the need for collaborative efforts, awareness, and supportive policies to promote agroecology effectively. The research contributes to bridging the gap between theoretical debates and practical applications of agroecology and urges rethinking and revising its conceptualization.